A lean‐zinc anode battery based on metal–organic framework‐derived carbon. Issue 4 (7th December 2022) - Li, Chao; Liang, Liheng; Liu, Xuhui; Cao, Ning; Shao, Qingguo; Zou, Peichao; Zang, Xiaobei
Abstract: Improving zinc metal (Zn 0 ) reversibility and minimizing the N/P ratio are critical to boosting the energy density of Zn 0 batteries. However, in reality, an excess Zn source is usually adopted to offset the irreversible zinc loss and guarantee sufficient zinc cycling, which sacrifices the energy density and leads to poor practicability of Zn 0 batteries. To address the above conundrum, here, we report a lean‐Zn and hierarchical anode based on metal–organic framework (MOF)‐derived carbon, where trace Zn 0 is pre‐reserved within the anode structure to make up for any irreversible zinc source loss. This allows us to construct low N/P ratio Zn 0 full cells when coupling the lean‐Zn anode with Zn‐containing cathodes. Impressively, high Zn 0 reversibility (average Coulombic efficiency of 99.4% for 3000 cycles) and long full‐cell lifetime (92% capacity retention after 900 cycles) were realized even under the harsh lean‐Zn condition (N/P ratio: 1.34). The excellent Zn reversibility is attributed to the hierarchy structure that homogenizes zinc ion flux and electric field distribution, as confirmed by theoretical simulations, which therefore stabilizes Zn 0 evolution. The lean‐Zn anode design strategy will provide new insights into construction of high‐energy Zn 0 batteries for practical applications. Abstract : A lean‐Zn and hierarchical anode material for low N/P ratio zinc metal batteries is reported for the first time. The innovative anode structure shows a large number of active sites and abundant ionic migration channels that jointly homogenize the ionic flux and electric field distribution, thus stabilizing Zn plating/stripping with high reversibility.